Malaria host candidate genes validated by association with current, recent, and historical measures of transmission intensity - Sepúlveda, N; Manjurano, A; Campino, S; Lemnge, M; Lusingu, J; Olomi, R; Rockett, K; Hubbart, C; Jeffreys, A; Rowlands, K; Clark, T; Riley, E; et al. (Oxford University Press, 2017)
Background:Human malaria susceptibility is determined by multiple genetic factors. It is unclear, however, which genetic variants remain important over time. Methods:Genetic associations of 175 high-quality polymorphisms within several malaria candidate genes were examined in a sample of 8096 individuals from northeast Tanzania using altitude, seroconversion rates, and parasite rates as proxies of historical, recent, and current malaria transmission intensity. A principal component analysis was used to derive 2 alternative measures of overall malaria propensity of a location across different time scales. Results:Common red blood cell polymorphisms (ie, hemoglobin S, glucose-6-phosphate dehydrogenase, and α-thalassemia) were the only ones to be associated with all 3 measures of transmission intensity and the first principal component. Moderate associations were found between some immune response genes (ie, IL3 and IL13) and parasite rates, but these could not be reproduced using the alternative measures of malaria propensity. Conclusions:We have demonstrated the potential of using altitude and seroconversion rate as measures of malaria transmission capturing medium- to long-term time scales to detect genetic associations that are likely to persist over time. These measures also have the advantage of minimizing the deleterious effects of random factors affecting parasite rates on the respective association signals.